2006
DOI: 10.1128/aac.50.5.1680-1688.2006
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Sensing Antagonistic Activities of Azithromycin in Pseudomonas aeruginosa PAO1: a Global Approach

Abstract: The administration of macrolides such as azithromycin for chronic pulmonary infection of cystic fibrosis patients has been reported to be of benefit. Although the mechanisms of action remain obscure, anti-inflammatory effects as well as interference of the macrolide with Pseudomonas aeruginosa virulence factor production have been suggested to contribute to an improved clinical outcome. In this study we used a systematic approach and analyzed the impact of azithromycin on the global transcriptional pattern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
223
3
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(257 citation statements)
references
References 56 publications
25
223
3
1
Order By: Relevance
“…Macrolide antibiotics have been shown to act as QS inhibitors at subinhibitory concentrations. For example, erythromycin has been reported to suppress production of P. aeruginosa hemagglutinins, protease, hemolysin and AHL signals [14], and studies have shown that azithromycin at sub-MIC concentrations affects QS-regulated virulence genes and biofilm formation in vitro [15][16][17] and in in vivo models of disease [18]. In the present study, we demonstrate that sub-inhibitory concentrations of azithromycin could dose-dependently reduce the haemolytic activity and biofilm formation in S. aureus.…”
mentioning
confidence: 56%
“…Macrolide antibiotics have been shown to act as QS inhibitors at subinhibitory concentrations. For example, erythromycin has been reported to suppress production of P. aeruginosa hemagglutinins, protease, hemolysin and AHL signals [14], and studies have shown that azithromycin at sub-MIC concentrations affects QS-regulated virulence genes and biofilm formation in vitro [15][16][17] and in in vivo models of disease [18]. In the present study, we demonstrate that sub-inhibitory concentrations of azithromycin could dose-dependently reduce the haemolytic activity and biofilm formation in S. aureus.…”
mentioning
confidence: 56%
“…These reductions coincided with reduced Las-and Rhl-dependent gene transcription and have been corroborated by microarray and proteomic studies (319,320), which found, in addition to QS gene misregulation, a reduction in levels of oxidative stress and motility-related genes but an increase in type III secretion (TTS)-related genes. The diminished response to oxidative stress conditions may account for the reduced cell viability in late stationary phase that was reported to occur with increasing concentrations of macrolides (318,319). Likewise, the finding that TTS was induced with exposure to AZM may explain the paradoxical finding that pretreatment of bacterial cultures with macrolides prior to intranasal inoculation in mice led to an enhanced lethal effect (321).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 72%
“…Since the use of fl uoroquinolones in young children is limited in many countries because of adverse neurological side effects, the clinical antimicrobial effectiveness against BLNAS and BLNAR NTHi in biofi lms has not been confi rmed. AMP, CTX, ERY and CLR had no signifi cant effect against either BLNAS or BLNAR NTHi biofi lms, although it has been reported that macrolides have an inhibitory effect on P. aeruginosa biofi lm formation and survival cells in biofi lm (Favre-Bonté et al 2003;Nalca et al 2006). …”
Section: Discussionmentioning
confidence: 93%